Effect of Spacing and Phosphate Fertiliser on Forage and Seed Yield of Dolichos Lablab Var. Lignosus - Verma, C M (Annals of Arid Zone, 2016)
Investigations on forage and seed production of Dolichos lablab var. lignosus as influenced by spacings and levels of phosphorus were carried out at the Central Arid Zone Research Institute, Jodhpur. Inter-row spacing of 25 cm resulted in maximum forage yield but the effect of spacing treatments on the seed yield was not well marked. ’Significantly higher fodder yields were obtain d with 40 and 80 kg P205/ ha over the control. Increase of the order of 2.0, 23.3 and 39.8 per cent in seed yield over control was recorded with the application of 20., 40 and 80 kg P205/ha respectively. Finally, the economic analysis of differential cost and return structure incidental to phosphatic fertilizer use indicated the usefulness of 40 kg P205/haâ€¢